2011
DOI: 10.1177/1059601111423532
|View full text |Cite
|
Sign up to set email alerts
|

Does Psychological Contract Breach Decrease Proactive Behaviors? The Moderating Effect of Emotion Regulation

Abstract: In a set of two studies, based on employees from two countries, we examined how emotion regulation moderates the relationship between psychological contract breach and (a) feelings of violation and (b) proactive behaviors (knowledge sharing and taking charge). We found that cognitive change buffers the negative effect of breach on feelings of violation and knowledge sharing (Study 1, United States). We replicate this result using taking charge as an outcome. In addition, we demonstrate that using high levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 95 publications
2
46
0
1
Order By: Relevance
“…Prior socialization and, in particular, work experiences may also shape preconceptions of the employment relationship. Previous experiences of psychological breaches, for instance, increase the risk that an individual will experience breaches again, maybe because of an increased reluctance to commit to and to feel highly obligated in an employment relationship (Robinson & Morrison, ) or because of emotion regulation strategies that increase awareness of employer actions (Bal, Chiaburu, & Diaz, ). Finally, pre‐entry organizational factors, such as recruitment communications and assessment processes, may also send signals regarding the expectations and obligations of the vacant organizational role.…”
Section: Discussionmentioning
confidence: 99%
“…Prior socialization and, in particular, work experiences may also shape preconceptions of the employment relationship. Previous experiences of psychological breaches, for instance, increase the risk that an individual will experience breaches again, maybe because of an increased reluctance to commit to and to feel highly obligated in an employment relationship (Robinson & Morrison, ) or because of emotion regulation strategies that increase awareness of employer actions (Bal, Chiaburu, & Diaz, ). Finally, pre‐entry organizational factors, such as recruitment communications and assessment processes, may also send signals regarding the expectations and obligations of the vacant organizational role.…”
Section: Discussionmentioning
confidence: 99%
“…Managing and delivering on the expectations of employees is one means of avoiding reductions in satisfaction and work engagement associated with PCB, but when PCs are breached organizations need to manage the implications for the job satisfaction and subsequent work engagement of employees lest employees reduce behaviors such as knowledge sharing, using initiative, etc. (Bal, Chiaburu and Diaz 2011). This may suggest approaches that limit the dissatisfaction associated with PCB, perhaps including effective communication of the reasons surrounding the breach, particularly where those reasons lie beyond the control of the organization.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Recently, Epitropaki (2013) investigated the interrelationship between psychological contract breach and organizational identification by considering procedural justice as a contextual variable. The psychological contract breach and psychological contract fulfillment are two conceptually different variables on a fulfillment-breach continuum (Bal, Chiaburu, & Diaz, 2011;Conway, Guest, & Trenberth, 2011); yet, psychological contract breach has different effects on employee outcomes as compared to psychological contract fulfillment (Conway et al, 2011). Previous research has shown various positive outcomes of psychological contract fulfillment, like affective commitment and in-role and extra-role performance (Chen, Tsui, & Zhong, 2008;Coyle-Shapiro & Kessler, 2002;Robinson et al, 1994;Zhao, Wayne, Glibkowski, & Bravo, 2007).…”
mentioning
confidence: 99%